Dynamic scenario simulation of dropwise condensation on a superhydrophobic surface with droplet jumping. (5th February 2019) - Meng, Kaixin; Fan, Wenli; Wang, Hao
Abstract: Dropwise condensation with coalescence-induced droplet jumping has been intensively studied. The coalescence dynamics between two droplets have been investigated, however, the complex interaction among the numerous droplets on the condensing surface remains less understood. This work conducts scenario simulation for the condensation process on structured hydrophobic surfaces. A number of droplets nucleate at prescribed nucleation sites on the surface, and then grow according to heat transfer equations and then coalesce with neighbors. The coalesced droplet is to jump or remain on the surface, depending on the absolute and also the relative size of the two coalescing neighbors. The gravity removal, as well as the sweeping downstream of the droplets, is also simulated. The simulation well reproduces the interaction scenario among the many condensing droplets. The simulated droplet size distribution is distinct from the widely used distribution that is based on the population balance theory, especially in that there are significant amounts of droplets have sizes beyond the critical jumping radius, which is highly consistent with experimental observations. The critical jumping radius is therefore not as important as expected. The optimization on the relative sizes and locations of the droplets could be the essential of further enhancement. The simulation method provides a powerful tool for large-scale condensation study.